2020
DOI: 10.1038/s41396-020-0726-z
|View full text |Cite
|
Sign up to set email alerts
|

Modular prophage interactions driven by capsule serotype select for capsule loss under phage predation

Abstract: Klebsiella species are able to colonize a wide range of environments and include worrisome nosocomial pathogens. Here, we sought to determine the abundance and infectivity of prophages of Klebsiella to understand how the interactions between induced prophages and bacteria affect population dynamics and evolution. We identified many prophages in the species, placing these taxa among the top 5% of the most polylysogenic bacteria. We selected 35 representative strains of the Klebsiella pneumoniae species complex … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
101
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(110 citation statements)
references
References 106 publications
(138 reference statements)
9
101
0
Order By: Relevance
“…for the transfer of temperate phages from one bacterial genome to another. We found that 97% of the strains were lysogens, with 86% being poly-lysogens, in line with our previous results in a much smaller dataset 26 . In total, 9886 prophages were identified in the genomes, with their 16,319 gene families accounting for 19.5% of the species pan-genome (Figure 1B).…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…for the transfer of temperate phages from one bacterial genome to another. We found that 97% of the strains were lysogens, with 86% being poly-lysogens, in line with our previous results in a much smaller dataset 26 . In total, 9886 prophages were identified in the genomes, with their 16,319 gene families accounting for 19.5% of the species pan-genome (Figure 1B).…”
Section: Resultssupporting
confidence: 92%
“…Instead, phages infecting bacteria with related serotypes might carry capsule depolymerases, which are known to act on di-or tri-saccharides 30-32 similar across these serotypes. This fits our previous studies on the infection networks of Kpn prophages 26 and suggests that a population of cells encoding and expressing a given serotype has more frequent phage-mediated genetic exchanges with bacteria of identical or similar serotypes (Figure 6A). In this context, phages carrying multiple capsule depolymerases have broader host range and may have a key role in phage-mediated gene flow between very distinct serotypes.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In the lytic cycle, the prophage is induced to produce progeny phages in response to chemical or physical stressors (4,5). Lysogenic phages or prophages are known to drive horizontal gene transfer (HGT) through transduction, but they also play an important role in increasing the genetic diversity of the host (6)(7)(8)(9)(10). Furthermore, defective prophages, also known as prophage-like elements, are stable in the host genome despite deleting most of the phage genes (6) and are known to increase host survival by conferring resistance against various stresses (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%